2021
DOI: 10.3389/fcvm.2021.630767
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of IL-32, IL-34 and IL-37 in Atherosclerosis: Speculative Role in Cardiovascular Manifestations of COVID-19

Abstract: Atherosclerosis, which is a primary cause of cardiovascular disease (CVD) deaths around the world, is a chronic inflammatory disease that is characterised by the accumulation of lipid plaques in the arterial wall, triggering inflammation that is regulated by cytokines/chemokines that mediate innate and adaptive immunity. This review focuses on IL-32, -34 and -37 in the stable vs. unstable plaques from atherosclerotic patients. Dysregulation of the novel cytokines IL-32, -34 and -37 has been discovered in ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 117 publications
(149 reference statements)
0
20
0
Order By: Relevance
“…Dysregulated IL-37 has been reported in a number of auto-immune diseases, e.g., rheumatoid arthritis (11), psoriasis, Grave's disease and systemic lupus erythematous, and in ulcerative colitis and Crohn's disease (12), and in gestational diabetes mellitus (13), acting perhaps via inhibiting the expression and function of pro-inflammatory cytokines (11,12,14). In addition, it has been well-reviewed that IL-37 substantially reduces the development of atherosclerosis (15), which has been confirmed in an IL-37 transgenic animal model (16).…”
mentioning
confidence: 99%
“…Dysregulated IL-37 has been reported in a number of auto-immune diseases, e.g., rheumatoid arthritis (11), psoriasis, Grave's disease and systemic lupus erythematous, and in ulcerative colitis and Crohn's disease (12), and in gestational diabetes mellitus (13), acting perhaps via inhibiting the expression and function of pro-inflammatory cytokines (11,12,14). In addition, it has been well-reviewed that IL-37 substantially reduces the development of atherosclerosis (15), which has been confirmed in an IL-37 transgenic animal model (16).…”
mentioning
confidence: 99%
“…In DM, TCF7 and GNAI2 were also upregulated, in addition to LAIR2 and IFITM3 . The known atherosclerosis gene IL32 27 was downregulated in DM+ compared to non-DM participants ( Figure 5B ). More systematic investigation of the overlap showed that 31 genes were significantly upregulated in both CAD and DM ( Table S6 for the genes expressed in at least 20% of the higher expressing cell type (pct.1 > 0.2).…”
Section: Resultsmentioning
confidence: 98%
“…IL-32 is a known atherosclerosis genes. 27,42 KLF2 is involved in Treg development, 43 but the detailed function of KLF2 in CD4T cells in the development of CAD has not been reported. CD48 on T cells enhances TCR signaling through cis interactions with CD2, LAT and Lck.…”
Section: Discussionmentioning
confidence: 99%
“…In DM, TCF7 and GNAI2 were also upregulated, in addition to LAIR2 and IFITM3 . The known atherosclerosis gene IL32 [ 21 ] was upregulated in DM- subjects compared to DM+ participants ( Figure 5 B). More systematic investigation of the overlap showed that 31 genes were significantly upregulated in both CAD and DM (see Table S6 for the genes expressed in at least 20% of the higher expressing cell type (pct.1 > 0.2)).…”
Section: Resultsmentioning
confidence: 99%